ANALISIS DISPARITAS PREKONOMIAN ANTAR PROVINSI DI INDONESIA - Vionita; Budi Marwoto, Pan; Astuti, Nelly (Jurnal Progresif Manajemen Bisnis, 2019)
This research was conducted by using an Tipology Klassen Method, Entrophy Method, dan Williamson Method. This research was conducted from March 2019 through June 2019 and It consict of 156 page without any the attachments. The research was conducted by using economic growth, economic contribution, dan gross domestic regional bruto. The Purpose of this research is to show comparison economic growth, economic contribution and the comparison of the absolut inter-provincial as well as provide clear information and certainty about the disparity that occurred in Indonesia by the method of Klassen Tipology, Entrophy and Williamson.The result of the analysis show economic growth on the Sumatera island 44,13%, Jawa island 33,19%, Nusa Tenggara island 10,87%, Kalimantan island 26,93%, Sulawesi island 6,04%, Maluku island 0,52% and Papua island 1,91%. Economic contribution on the Sumatera island 22,02%, Jawa island 58,52%, Nusa Tenggara island 3,12%, Kalimantan island 7,86%, Sulawesi island 6,04%, Maluku island 0,52% and Papua island 1,91%.The comparison of the absolut inter-provincial show (the province of the West Sumatera, jambi, and Riau Island: quadran 3 through quadran 4), (the province of the South Sumatera: quadran 4 through quadran 2), (the province of the East Jawa: quadran 1 through 4), (the province of the Banten: quadran 1 through quadran 2), (the province of the Central Sulawesi and North Maluku: quadran 4 through quadran 3), and (the province of the South Sulawesi: quadran 3 through quadran 2). The result of the analysis the disparity was conducted by using Williamson method show disparity in indonesia is still very high of 0,7503 and Entrophy method show disparity in indonesia of 0,81 and tend to be no movement.